Análise do frequency-following response em crianças com sífilis congênita - Lemos, Fabiana Aparecida (2020)
Introduction: Congenital syphilis is considered a risk indicator for hearing loss in children, but the real impacts caused by syphilis on these children over their general development, including hearing, are still unknown. Objectives: Study1: To verify the parameters used to acquire the frequency-following response (FFR) response in children up to 24 months of age through systematic review; Study 2: Analyze the results of the frequency-following response in children with congenital syphilis. Method: In study 1: The protocol was registered in PROSPERO, following the recommendations of PRISMA. The research was carried out by two independent reviewers in six databases (LILACS, Livivo, psycINFO, PubMed, Scopus, Web of Science); gray literature (Google Scholar, Open Gray, Proquest) and manual searches on bibliographic references. In study 2, the sample consists of nine children with congenital syphilis (EG) and five children without syphilis (CG), aged between 12 and 24 months. All participants present responses in the Brainstem Auditory Evoked Potential at 80 dB nNA and transient evoked otoacoustic emissions present. They performed the FTA-ABS laboratory test from the age of 18 months and the FFR with stimulus / da /, with a duration of 170 ms, speed of 3.70 / s, at an intensity of 80dBnNA in both ears. Results: In study 1: 459 studies were identified. After reading the full text, 15 studies were included. Seven studies were classified as low risk of bias, seven as moderate risk and one as high risk. In study 2: There was no difference between the groups studied in the analysis of parameters of the time and frequency domain in the FFR response. Conclusion: Study 1: There is a consensus in the use of some parameters of acquisition of the FFR with speech stimulus, such as vertical mounting of electrodes, alternating polarity, the sampling rate of 20,000 Hz, the syllable / da / synthesized stimulus and the 40 ms duration stimulus. Although these parameters have a consensus, the results show the lack of a single protocol established for the acquisition of data for the collection of the frequency-following response with speech stimulus in children in the investigated age group. Study 2: Children aged 12 to 24 months with notification of congenital syphilis at birth have the same pattern of central auditory neural response assessed by the FFR as children without congenital syphilis.